Implementation of Marriage Pillars According to Syafi'iyah Fiqh in Bandar Dua District, Pidie Jaya Regency: (Study of Marriage Witness Justice) - Bukhari; Danial; Munadi Usman (Institut Agama Islam Al-Aziziyah Samalanga, 2023)
Witnesses in a marriage contract are pillars that affect whether a marriage is valid or not. A just witness is someone who does not commit major sins and also does not perpetuate himself with minor sins. For this age, getting a fair witness is definitely very difficult. However, the phenomenon that occurred in the field was not the case. Witnesses for marriage are often chosen based on their position and closeness to the bride and groom's family, not based on criteria outlined in fiqh law. This is very fatal for a marriage because if a marriage contract seems to be neglected, then unknowingly there will be prolonged adultery. For this reason, the author wants to study this problem scientifically. The formulation of the problem in this study is how is the implementation of the pillars of marriage in Bandar Dua, Pidie Jaya Regency according to Islamic law, and what is the urgency of justice for marriage witnesses and their impact on families in Bandar Dua District, Pidie Jaya Regency. Through the form of qualitative research, descriptive analysis techniques and inductive methods are the main techniques in tracing data and facts to be examined and find answers to the formulation of problems that have been defined. The result of the research is that the implementation of the pillars of marriage in the Bandar Dua District in general is in accordance with the Syafi'iyah fiqh. But there are a number of things that still need attention, namely related to the justice of marriage witnesses. Of the four elements of the assessment ‘adālah witnesses to marriage, there is one that is often missed in the assessment, namely maintaining marwah. Even though someone who doesn't protect his dignity is also considered wicked, and loses his justice. In general, the sources (counselors, young priests, community leaders, religious leaders, village heads, marriage guardians, married couples, and also wedding witnesses) denied that there was a strict selection of marriage witnesses. The urgency of witness justice for a married family is very clear because it is indeed a pillar of marriage. From a moral point of view, the presence of fair witnesses is also able to maintain the integrity and harmony of the family. Spiritually speaking, the presence of two just witnesses can also bring blessings and kindness to the bride and groom, because generally two people who are considered just are two pious people.